Testicular morphology of adult wistar rats treated with Rudgea viburnoides (Cham.) Benth. leaf infusion - Juliana Castro Monteiro (Brazilian Archives of Biology and Technology, 2012)
The present study was carried out to investigate the effects of Rudgea viburnoides infusion on the body biometry and testicular morphometry and stereology of adult Wistar rats. Two groups received the infusion daily at the concentration of 3 or 6 mg/mL for 40 days. The control group received only water. Neither the biometrical parameters nor the tubular diameter and the height of the seminiferous epithelium showed any significant alterations in the treated animals. Leydig cells stereology did not show any significant alterations in the treated animals. These results indicated that R. viburnoides did not cause alterations in body biometry and testicular morphometry.